Requirements for facility premises and equipment in accordance with the HACCP system - Skrynnyk, Ilona; Kuzmin, Oleg (My University, 2022)
The purpose of the work is to develop a plan of requirements for premises and equipment in accordance with the principles of HACCP. Метою роботи є розробка плану вимог до приміщень та обладнання відповідно до принципів НАССР.
Keywords: кафедра технології ресторанної і аюрведичної продукції; restaurant establishment; HACCP; заклад ресторанного господарства